Development of A Base Learning Project Model With Online Media In An Effort to Increase Learning Activities During the COVID-19 Pandemic - M Martiano; H Maulana (Institute of Computer Science, 2021)
Decrease in learning outcomes in operating systems courses. The decline in learning outcomes is caused by the current corona virus pandemic. Which causes face-to-face lectures to be online. Researchers use project base learning to improve learning outcomes. The application consists of 2 cycles, namely Diclus 1 which is 80.12% with the number who did not pass, namely 16 students, researcher evaluating the learning process so that in cycle 2 it increased by 83.73%. With the student’s who did not pass. It can be concluded that the base learning method can be used to improve learning outcomes during the COVID-19 pandemic.